A critical investigation of the Primary Schools Nutrition Programme (PSNP) in the Eastern Cape - Houston, Elizabeth Margaret (Rhodes University, Faculty of Humanities, Department of Political Studies, 1997)
The thesis focuses on the Primary School Nutrition Programme (PSNP), particularly in the Eastern Cape, as a government nutrition and education project, and its failure to achieve its stated goals. The programme experienced problems almost as soon as it was introduced. The press reported incidents of fraud and maladministration and the programme was halted and restarted numerous times. The thesis seeks to offer some insight as to why the government was unable to reach its stated objectives in the implementation phase of the programme. State theory informs the thesis in an attempt to further explain why governments often seem unable to attain their intended goals. The thesis provides an alternative to government development programmes, arguing that NGOs are better equipped to deal with the particular problems that people on the ground experience when dealing with issues like nutritional vulnerability. Operation Hunger provides an excellent case study for how development of this nature ought to occur. The essential argument of the thesis is that there is an inherent tension between what a government's stated intentions is and what, it, in reality, intends to gain from such programmes. It is the contention of this thesis that the Government of National Unity embarked on the PSNP, not to ensure nutritional development for its own sake, but rather to curry favour with its constituents. Operation Hunger, and other organisations like it, provide relief to vulnerable communities with no hidden agenda in mind. Their mandate is solely that they provide assistance. The thesis argues, then, that NGOs have a role in domestic and international politics, that they can make up for or do better, or at least well, things that governments struggle to do.
Keywords: Operation Hunger (Organization)|Primary schools nutrition programme -- South Africa|Non-governmental organizations|School children -- Food -- South Africa